Study of Artificial Intelligence Development in Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Spreading new digital technologies have an increasing impact on modern civilization, in particular artificial intelligence. AI technologies are changing processes in industry, energy, education, health care and banking, as well as affecting the mobility of the population. It is predicted that AI technologies will lead in the future to significant economic shifts caused by the growth of labor productivity due to the use of machines that are able to perform new functions, and this in turn will accelerate the transition of the world economy to the path of sustainable development.